Formulation, Characterization and In-vitro Evaluation of Cetrizine HCL Oral Disintegrating Tablets - PASUPULATI, HARITHA; PHALGUNA, Y; RUDRA, SANDHYA (Asian Journal of Pharmaceutical Research and Development, 2019)
The main objective of this work is to formulate and evaluate Cetirizine HCl MFDT’s using different concentrations of superdisintegrants like croscarmellose sodium (CCS), sodium starch glycolate (SSG) and their combinations in different ratios. The in vitro disintegration time of Cetrizine Hcl prepared by direct compression method by super disintegrates were found to be in the range of 18 to 11sec fulfilling the official requirements. The bulk density and tapped bulk density for the entire formulation blend varied from 0.508 gm/cc to 0.5438 gm/cc and 0.5941 to 0.6408 respectively. The friability was found in all designed formulations in the range 0.42 to 0.74% to be well within the approved range (<1%). The weight variation was found in all designed formulation in the range 97 to 102 mg. The wetting time were found to be in the range of 11 to 18sec. Water absorption ratio for all the formulations found in the range 11 to 16%.combination of sodium starch glycolate and cross carmellose sodium (6% of 25%-ssg&75%ccs)) promotes dissolution rate of drug release when compared to formulation of SSG & CCS alone. It may be due to capillary and wicking mechanism of SSG & CCS. Keywords: